Novel partial duplication of EYA1 causes branchiootic syndrome in a large Brazilian family. (September 2015) - Dantas, Vitor G.L.; Freitas, Erika L.; Della-Rosa, Valter A.; Lezirovitz, Karina; de Moraes, Ana Maria S.M.; Ramos, Silvia B.; Oiticica, Jeanne; Alves, Leandro U.; Pearson, Peter L.; Rosenberg, Carla; Mingroni-Netto, Regina C.
Abstract Objective: To identify novel genetic causes of syndromic hearing loss in Brazil. Design: To map a candidate chromosomal region through linkage studies in an extensive Brazilian family and identify novel pathogenic variants using sequencing and array-CGH. Study sample: Brazilian pedigree with individuals affected by BO syndrome characterized by deafness and malformations of outer, middle and inner ear, auricular and cervical fistulae, but no renal abnormalities. Results: Whole genome microarray-SNP scanning on samples of 11 affected individuals detected a multipoint Lod score of 2.6 in the EYA1 gene region (chromosome 8). Sequencing of EYA1 in affected patients did not reveal pathogenic mutations. However, oligonucleotide-array-CGH detected a duplication of 71.8Kb involving exons 4 to 10 of EYA1 (heterozygous state). Real-time-PCR confirmed the duplication in fourteen of fifteen affected individuals and absence in 13 unaffected individuals. The exception involved a consanguineous parentage and was assumed to involve a different genetic mechanism. Conclusions: Our findings implicate this EYA1 partial duplication segregating with BO phenotype in a Brazilian pedigree and is the first description of a large duplication leading to the BOR/BO syndrome.